NEUTRONIC DESIGNS OF AP1000 REACTOR USING URANIUM DIOXIDE AND REACTOR GRADE PLUTONIUM FUELS - NIM: 20214051, NAILATUSSAADAH
Neutronic designs of AP1000 reactor using Uranium Dioxide and Reactor Grade Plutonium fuels have been conducted. This study evaluated the standard of Westinghouse AP1000 reactor and ZrB2 as Integral Fuel Burnable Absorber (IFBA). Different fuel compositions of assembly type were analyzed in by using SRAC 2006 code system with JENDL 4.0 nuclear data library. This study aiming to compare the neutronics characteristics of reactor core using uranium dioxide and MOX (with Reactor Grade Plutonium) fuels. Some results of the study show that optimal criticality of this reactor can be achieved by some core designs with the results of k-eff are 1,0722; 1,1011; 1,0895 and 1,0998.